2008
DOI: 10.1007/s11940-009-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Allodynia as a complication of migraine: Background and management

Abstract: Allodynia is a normal part of the untreated migraine attack in most people with episodic migraine and is prevalent in chronic migraine. The extent to which allo-dynia contributes to the pain and disability of migraine attacks is unclear, as is its clinical importance. The presence of allodynia correlates with the severity and other features of migraine, including aura, migraine-associated symptoms, and motor symptoms. The development of allodynia is associated with resistance to triptan treatment. It is uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Numerous studies, using quantitative sensory testing (QST) and/or a questionnaire [see (1,2) for review], have now reported CA in episodic migraine patients, although with very different prevalence. Using a semistructured interview, CA was found in 50-75% of episodic migraine patients (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies, using quantitative sensory testing (QST) and/or a questionnaire [see (1,2) for review], have now reported CA in episodic migraine patients, although with very different prevalence. Using a semistructured interview, CA was found in 50-75% of episodic migraine patients (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…1). The significant presence of cephalic, cervical, and remote sensory hyperalgesia in patients with CWAH mirrors the presentation of primary headache 15,[17][18][19][20][21][22][83][84][85][86][87]94 and is considered a clinical manifestation of central sensitization. 19,95,96 Given this centrally-sensitized environment, the augmentation of light-induced pain in our CWAH group is not surprising.…”
Section: Discussionmentioning
confidence: 97%
“…). The significant presence of cephalic, cervical, and remote sensory hyperalgesia in patients with CWAH mirrors the presentation of primary headache and is considered a clinical manifestation of central sensitization …”
Section: Discussionmentioning
confidence: 99%
“…Many methods, including clinical questionnaires, are available to assess the pain morbidity caused by allodynia, but we still lack an objective framework with which to quantify the pain invoked by the allodynia. The contribution of allodynia to the pain morbidity and disability resulting from migraine attacks is still unclear (Young, ). More studies are needed to investigate the exact mechanisms that lead to the extracephalic (body pain) symptoms during migraine attacks.…”
Section: Introductionmentioning
confidence: 99%